ANALISIS MEKANISME TRANSMISI KEBIJAKAN MONETER JALUR NILAI TUKAR DENGAN PENDEKATAN VECM PERIODE 2005:1-2012:12 - Nurobi Goldiman Wardianda; Dian Octaviani R (Jurnal Ekonomi Trisakti, 2022)
This thesis discusses about analysis of transmission mechanism of monetary policy through exchange rate channel in Indonesia, during the period 2005:1 - 2012:12. By using variables such as PUAB Interest Rate, Exchange Rate, Total Export, National Income and Price lndex. The method's try to used in this thesis is a method of Vector Error Correction Models (VECM). This research aims to know the effectiveness of transmission mechanism of monetary policy through exchange rate channel within respect to see the influence of the operational targets (PUAB Interest Rate) to the intermediary target (Exchange Rate), as well as the final goals of monetary target (national income and price level). The results of this research show the transmission mechanism of monetary policy through exchange rate channel path deserves to be researched further, it is based on the significant value of the t-test, f-test, and Adj R2. Meanwhile, the results of the analysis of the "Impulse Response" found that the influence of shock caused by PUAB Interest Rate will cause the depreciation of Exchange Rate and also increasing of total export, we can visible to see the direct mechanism from Interest Rate to Exchange Rate (monetary sector) and after that transmitted to the real sector through the Total Export. As seen from the analysis of Variance Decomposition can be stated that during the period 2005:1-2012:12, the National Income variance contribution donated by Total Export and Exchange Rate, While Price Level variance contribution rate donated by Exchange Rate and PUAB Interest Rate